Kearifan Lokal dan Perilaku Sosial dalam Ritual Adat Nokeso Suku Kaili di Desa Binangga Sebagai Sumber Pembelajaran Sejarah - Mahid, Andriansyah (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
This paper aims to discuss the social behavior of the Kaili tribe in preserving culture through the Nokeso traditional ceremony which contains local wisdom values. The subject of this study is the Kaili tribe community, especially teenagers in Binangga Village, Marawola District, Sigi Regency. This is based on the weakening of cultural preservation and the lack of knowledge of Kaili tribe teenagers about local culture, especially in the Nokeso traditional ceremony. Nokeso is a traditional ceremony that is routinely carried out by the Kaili tribe when entering adolescence. Through a qualitative method with the approach used by Max Weber about social action or social behavior, it shows how social culture, namely the Nokeso traditional ceremony, is starting to be abandoned, there is a cultural shift towards the social behavior of Kaili tribe teenagers in Binangga Village which is caused by a lack of understanding of the values ​​in the Nokeso traditional ceremony tradition. Through this study, it was revealed that the Nokeso traditional ceremony is one of the local wisdoms of the Kaili tribe which has character values, namely Nogase Ngisi or brushing teeth is related to the values ​​of politeness and honesty. Nijunu or bathing has the value of self-purification, Niponda or carrying on the shoulder is a responsible character and Motodu Lanjara which is the activity of stepping on stairs gives the meaning of the value of purity, guarding the gaze, and protecting the genitals from negative things.Keywords: Local Wisdom, Social Behavior, Nokeso Traditional Ritual, Kaili Tribe